39 A qualitative study of family carer's attitudes towards agitation in people with moderate/severe dementia. Issue 3 (1st September 2017) - Stringer, Aisling; Pritty, Elizabeth; Laybourne, Anne; Frenais, Francesca La; Higgins, Shanlee; Doyle, Mary-Jo; Leavey, Gerry; Livingston, Gill; Sampson, Elizabeth
Abstract : Background: People with severe dementia are often cared for at the end of life in nursing homes or acute hospital wards. In these circumstances, symptoms of agitation such as shouting, aggression, and restlessness are common. Agitation is distressing for the person with dementia and paid and family carers, and it is associated with poorer quality of life. Little is known about the attitudes that family carers have towards agitation in severe dementia. Such attitudes are important because they contribute to the personhood and quality of life of the person living with dementia. Aims: To develop knowledge of the attitudes, explanatory models, and coping strategies of family carers around agitation in people with dementia receiving end of life care in hospitals or nursing homes. Methods: Across two acute hospital and two nursing home sites, we conducted semi-structured interviews with eight family carers of people with a clinical dementia rating of 2 or 3 (moderate/severe). Interview transcripts were open coded by two researchers. Using an iterative process, our open coding was developed into key themes related to explanatory models and coping strategies. Results: Preliminary analysis showed that agitation was often attributed to disease pathology rather than the individual. Coping strategies included limiting visits to times when the person with dementia was unlikely to be agitated. Conclusion: Family carers see agitation in people with severe dementia at the end of life as a part of their illness and separate to their personal identity. This functioned as a means of preserving the individual's personhood.